A Comprehensive Survey of Preference for Personal Health Record Features in Patients with Diabetes. Issue 1 (September 2020) - Knisely, Benjamin M.; Vaughn-Cooke, Monifa
Individuals with diabetes often do not adequately adhere to self-management regimens. Personal Health Record (PHR) systems can aid patients with diabetes in managing their disease by encouraging patient provider communication, providing education and lifestyle information, and providing tools for disease management. While demonstrated to be a useful tool, PHR acceptance among chronic disease patients is low. This study investigated the influence of certain patient characteristics on interest in PHR features. Patients were asked to rate how often they would likely use certain PHR features. Statistical analysis was performed on the data. The analysis revealed several patterns regarding desired features for patients with respect to patient knowledge, technology experience, and health state. Designers of these systems should consider how these factors can influence system use. Strategies for encouraging patients to continually use these systems should also be considered.